A car as an object of tax and customs duties in the Russian Federation - A. V. Savtsova; O. N. Patsenko; A. A. Domarev; M. E. Volostnikov (Вестник Северо-Кавказского федерального университета)
Introduction. A car as an object of tax and customs duties in the Russian Federation is under close attention of the legislator in this area, and this interest will only grow due to an increase in the number of vehicles. According to experts and car owners, taxation and taxation of transport  with customs duties has  a  number  of  significant disadvantages. Goal.  The purpose  of  the  work  is  to identify  the  main problems  of  a  low level of collection of transport tax and excessive utilization fee, and to study the prospects for their optimization. Materials and methods. The methods of analysis, synthesis, formal logic, comparison, induction, deduction, and other are used. Results and discussion. The basics of vehicle taxation are  considered,  a  comparative  analysis  of  transport tax and  fee  rates  in different  countries  (Great  Britain,  Australia  and  Denmark)  is carried  out in order to increase their collection on the territory of the Russian Federation. Conclusion. A mechanism for increasing revenue from taxation of vehicles, taking into account the environmental component, is proposed.